Improving the physical distribution or logistics systems for ACI mosquito coils during peak and semi-peak seasons - Chowdhury, Farhana Sharmim (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2013.